Website-Based Marketing Information System for UMKM Products at Asaul Store Using the ADDIE Method - Ifan Zamorano; Uce Indahyanti (CV. Media Digital Publikasi Indonesia, 2025)
MSMEs (Micro, Small, and Medium Enterprises) have an important role in the economy, but often face challenges in marketing their products widely. Marketing is a crucial aspect in the development of MSMEs, especially in today's digital era. However, many MSMEs still experience obstacles in reaching a wider market due to limitations in traditional marketing methods. Toko A'saul, an MSME business, uses a website-based information system to market its products, which effectively increases the marketing reach and competitiveness of its products. Website-based marketing has a positive impact on increasing the sales and market reach of MSMEs. In addition, this system allows MSMEs to compete better with larger businesses in the digital market. Through the implementation of a web-based marketing platform, MSMEs are expected to maximize their potential in attracting new customers, expanding market share, and improving overall business performance. In addition, the platform increases customer satisfaction by offering a better shopping experience and more responsive services.